2000
DOI: 10.1089/jop.2000.16.519
|View full text |Cite
|
Sign up to set email alerts
|

Impression Cytology of Pterygium

Abstract: The purpose of this study was to study the morphology and cytokeratin expression in the epithelia of pterygia. Impression cytology and immunohistochemical staining with antikeratin antibodies were performed in 32 eyes of 16 patients with pterygia. TUNEL stain and electron microscopy were also performed in surgical specimens ofpterygium. Squamous metaplasia-like epithelial cells were found in all specimens of impression cytology, especially in the head part. These specimens had positive immunostaining by antipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
16
0
2
Order By: Relevance
“…5,6,14 On the other hand, the epithelium of pterygium may display squamous metaplasia. 15 In addition, adjunctive alkylating antineoplastic agent or radiotherapy is usually required to prevent the high recurrent rate in the treatment of pterygium. 16,17 Furthermore, the presence of oncogenic viruses, 18 loss of heterozygosity, 19 and abnormal expression of p53 in pterygium tissues 20 suggest possible neoplastic nature of pterygium.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,14 On the other hand, the epithelium of pterygium may display squamous metaplasia. 15 In addition, adjunctive alkylating antineoplastic agent or radiotherapy is usually required to prevent the high recurrent rate in the treatment of pterygium. 16,17 Furthermore, the presence of oncogenic viruses, 18 loss of heterozygosity, 19 and abnormal expression of p53 in pterygium tissues 20 suggest possible neoplastic nature of pterygium.…”
Section: Discussionmentioning
confidence: 99%
“…A stromal overgrowth of fibroblast and blood vessel is accompanied by an inflammatory cell infiltrate and abnormal extracellular matrix accumulation [3][4][5][6]. Although several hypotheses have been associated with its etiology, its pathology still remains to be explained.…”
Section: Introductionmentioning
confidence: 99%
“…Bias was reduced by masking the cytologists and pathologists. Previous studies of IC samples obtained from pterygia surfaces have reported conjunctival squamous metaplasia and goblet cells without atypical cells (18)(19) . However, IC analysis of subclinical intraepithelial OSSN has already been described.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, it is difficult to diagnose these patients based on clinical characteristics alone (15) . Impression cytology (IC), a method for the evaluation of superficial cell layers in the diagnosis (16) and treatment follow-up of several ocular surface tumors (17) , has exhibited squamous metaplasia with goblet cells in specimens obtained from pterygia (18)(19) . A graded series of ocular surface changes has been described throughout the bulbar conjunctiva, with the most advanced changes occurring directly over the pterygium surface, confirming that pterygium is indeed an ocular surface disorder (18) .…”
Section: Introductionmentioning
confidence: 99%